- #1

- 38

- 0

I keep getting stuck on one part of the equation. can somebody help?

dy/dx = y(xy

dy/dx = xy

dy/dx + y = xy

u = y

y = u

dy/dx = dy/du * du/dx

dy/dx = -3u

Substituting terms into the original equation

-3u

Here is where I get stuck. When I divide u

dy/dx = y(xy

^{3}- 1)dy/dx = xy

^{4}- ydy/dx + y = xy

^{4}u = y

^{1-n}= y^{-3}y = u

^{-3}dy/dx = dy/du * du/dx

dy/dx = -3u

^{-4}du/dxSubstituting terms into the original equation

-3u

^{-4}du/dx + u^{-3}= x(u^{-3})^{4}Here is where I get stuck. When I divide u

^{-4}to clean up the equation, the right hand side still has u^{-8}remaining. I will not be able to go on since the right hand side can only have x terms. What am I doing wrong?
Last edited: